Being born after your brother is not a disadvantage: Reproductive success does not depend on the sex of the preceding sibling. Issue 5 (25th March 2015) - Puskarczyk, Karolina; Galbarczyk, Andrzej; Klimek, Magdalena; Nenko, Ilona; Odrzywołek, Ludwik; Jasienska, Grazyna
<x xml:space="preserve">Abstract</x> Objectives The aim of the present study is to examine whether being born after a brother versus after a sister differentially impacts reproductive outcomes in a contemporary population. The sex of the preceding sibling may influence an individual's fitness, and, in fact, individuals born after a brother have been shown to have lower reproductive success in historical populations. Males, as the more expensive sex, constitute a drain on maternal resources and elicit an immune response during pregnancy, which may have negative consequences on subsequent siblings. Methods A questionnaire was used to collect data on reproductive health and family history from 951 women and 380 men between 20 and 92 years of age in villages throughout the Mogielica Human Ecology Study Site in southern Poland. Number of children, number of sons and daughters, age at menarche, age at marriage, age at menopause, and age at first and last reproduction were tested as components of reproductive success. Results The sex of one's preceding sibling had no statistically significant impact on any of the reproductive characteristics tested. Conclusions Our results suggest that potential immunological and nutritional disadvantages experienced during prenatal life by individuals born after male siblings do not have long‐lasting effects in modern, well‐nourished populations. Am. J. Hum. Biol. 27:731–733, 2015. © 2015 Wiley Periodicals, Inc.